High Frequency Regeneration of Phalaenopsis amabilis (L.) Bl. cv. Lovely through In vitro Culture - Sinha, Pinaki; Jahan, Miskat Ara Akhter; Munshi, John Liton; Khatun, Rahima (Plant Tissue Culture and Biotechnology, 2011)
Young leaf explants from mature plant of Phalaenopsis amabilis cv. Lovely were cultured on half strength of MS supplemented with BA (2.0 mg/l), NAA (0.5 mg/l), 2% (w/v) sucrose, 10% (v/v) coconut water, 2 g/l peptone and 1 g/l activated charcoal. Each section of explant produced ten protocorm-like bodies (PLBs) after 12 weeks of culture. The PLBs were subcultured on the same nutrient medium but without phytohormone and addition of 150 mg/l L-glutamine, where PLBs were found to be enlarged with leafy shoots and new PLBs were induced from the base of the old ones. Plantlet development from leafy shoots was achieved on half strength MS supplemented with 2 g/l peptone, 2% (w/v) sucrose, 10% (v/v) CW and 1 g/l activated charcoal, where 100% explants were developed into plantlets with roots within eight weeks. The addition of 2.5 g/l banana powder enhanced the number and length of roots. Within the first 32 weeks after initiation of culture about 1200 plantlets as well as a huge amount of PLBs were achieved from a single explant section. The plantlets were acclimated in natural environment. Key words: Orchid, Phalaenopsis amabilis, Protocorm-like bodies, Clonal propagation D.O.I. 10.3329/ptcb.v20i2.6913 Plant Tissue Cult. & Biotech. 20(2): 185-193, 2010 (December)